2009
DOI: 10.1002/hep.22760
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface antigen levels: A guide to sustained response to peginterferon alfa-2a in HBeAg-negative chronic hepatitis B # †

Abstract: We investigated the relationship between hepatitis B virus surface antigen (HBsAg) serum level decline and posttreatment response in patients with hepatitis B e antigen (HBeAg)-negative chronic hepatitis B from a large multinational study of pegylated interferon alfa-2a (peginterferon alfa-2a), with or without lamivudine, versus lamivudine alone. Serum HBsAg was quantified using the Architect assay (Abbott Diagnostics) at pretreatment, end of treatment (week 48), and 6 months after the end of treatment (week 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
450
4
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 436 publications
(486 citation statements)
references
References 39 publications
24
450
4
6
Order By: Relevance
“…[10][11][12] Moucari et al 13 reported that an early drop in qHBsAg was highly predictive of a sustained virological response (SVR) in HBeAg(À) patients. This was similar to the results obtained by Brunetto et al, 14 who found that an on-treatment decline of qHBsAg was significantly associated with sustained HBsAg clearance.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…[10][11][12] Moucari et al 13 reported that an early drop in qHBsAg was highly predictive of a sustained virological response (SVR) in HBeAg(À) patients. This was similar to the results obtained by Brunetto et al, 14 who found that an on-treatment decline of qHBsAg was significantly associated with sustained HBsAg clearance.…”
supporting
confidence: 92%
“…A 1 log IU/mL drop in qHBsAg at week 24 of therapy was shown to predict SVR (NPV ¼ 97%, PPV ¼ 92%), and a low qHBsAg level at week 48 with an on-treatment decline > 1 log IU/mL was shown to be associated with sustained HBsAg clearance. 13,14 In contrast, the clinical usefulness of qHBsAg in patients receiving oral nucleos(t)ide analogues remains largely unknown; previous studies have investigated the relevance of qHBsAg in patients treated with LAM or adefovir, which are known to be less potent agents. 4,6,9 Furthermore, for the most part, the available data were not derived from independent studies but were incorporated into studies in which either a combination was used or a comparison with PEG-IFN was made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have demonstrated that on-treatment HBsAg quantification is a useful tool to predict the response to Peg-IFN treatment, whereas its role during NA treatment has been scarcely investigated [15][16][17][18][19]. Gramenzi et al studied HBsAg kinetics in the sera of 42 HBeAg-negative patients treated with LAM monotherapy for a prolonged period and found that in six on-treatment responders, lamivudine was associated with a steady HBsAg decrease up to its disappearance in two cases [20].…”
Section: Discussionmentioning
confidence: 99%